Smile Design pada Penutupan Diastema Menggunakan Veneer Porselin pada kasus Protrusif (Laporan Kasus) - Elline Elline (Jurnal Kedokteran Gigi Terpadu, 2019)
Background:  Value of the appearance of one’s teeth has taken on a greater importance in today’s society. Several Choices of treatment are available to treat the problems arising in the zone of high esthetic sensitivity. Each treatment offers some advantages and disadvantages. The use of porcelain laminate veneers to solve esthetic and functional problems has been shown to be a valid management option especially in the anterior esthetic zone. Smile design is a scientific principal that can help operators to achieve esthetic goals. This case report discussed a patient with diastema in the anterior region with protrusive dental position. The patient was treated with porcelain laminate veneers in the anterior teeth for diastema closure. Objective: This case report was written to bring forward the proper and successful management in esthetic treatment of anterior maxilla in protrusive dental position case. Case and management : A 37 year-old female patient complained of diastema in anterior teeth and feels uncomfortable with her condition. She was unhappy with the appearance of her teeth and restrained herself from smiling due to self-consciousness. On examination, diastemas were found in her maxillary and mandibular anterior region. Smile Design was applied in this patient, and it was decided to use porcelain laminate veneer. The tooth preparation was kept in enamel at a depth of 0.5 mm using a depth cutting diamond and a tapered diamond 1 mm in diameter. 0.25 mm chamfer was maintained in the cervical region The chamfer finish lines were at the level of gingival margin. Gingival retraction procedure was performed prior to final dental impression using a double impression technique. Cementation was done after final evaluation of both aesthetic and function. Conclusion: Esthetic management in diastema closure  using simple smile design can be done by using porcelain laminate veneers which give satisfactory result.